Effect of hormonal pre-treatment on sprouting and survival of different medicinal plant species - RAJ KUMAR SINGH TIWARI; RAJENDRA MEHTA; SANJEEV KUMAR (Smujo International, 2015)
Abstract. Tiwari RKS, Mehta R, Kumar S. 2015. Effect of hormonal pre-treatment on sprouting and survival of different medicinal plant species. Nusantara Bioscience 7: 77-89. In the present study, sprouting and survival of cuttings of ethnomedicinally important shrub species i.e. Argyreia nervosa, Gardenia gummifera, Helicteres isora, Hiptage madablota, Lippia javanica, Caesalpinia bonduc, Jasminum grandiflorum, Millingtonia hortensis, Putranjiva roxburghii, Stereospermum suaveolens, Vitex negundo, Vitex leucoxylon, and Zanthoxylum armatum were recorded through propagation. In vivo, experiment was conducted comprising treatments of cutting diameters i.e. thick (D1-2.1 cm), medium (D2-1.6 cm) and thin (D3-0.8 cm) and pre-treatment of exogenous hormones viz., Rootex, ?-Naphthalene Acetic Acid (NAA) and Indole 3 Butyric Acid (IBA) maintained at 1000 ppm in talc powder formulation. Results revealed a significant effect of cutting diameter and pre-hormonal treatment on sprouting and survival of medicinal plant species under greenhouse conditions. Species i.e. L. javanica, V. negundo, V. leucoxylon, H. isora, C. bonduc, G. gummifera, and S. suaveolens had higher percent of sprouting (84.25-100.0) and survival (59.72-100.0). Effect of all three hormones on all the three diameters of plants cuttings for sprouting and survival was significant and clearly distinctive with maximum increase of 66.66 and 64.81 respectively in species C. bonduc. IBA had its more effect on sprouting and survival of most of the medicinal plant species in comparison of Rootex and NAA.